Positioning and revision of CCUS technology development in China. (March 2016) - Li, Q.; Chen, Z.A.; Zhang, J.-T.; Liu, L.-C.; Li, X.C.; Jia, L.
Graphical abstract: Highlights: Positioning and analysis of China's CCUS development is presented. Influential factors of China's future CCUS technology development are summarized into three aspects. Key suggestions for China's CCUS RD&D in the future are provided. Abstract: CCUS technology has the potential to reduce emissions substantially from the whole lifecycle of traditional energy-intensive industry on a large-scale basis. A summary of the current status of CCUS in China is viewed as a necessary background and a starting point for the content of the following paper. Next, the positioning and analysis of China's future CCUS development are presented by answering the following questions "Why does China need CO2 utilization?" and "How much of the CO2 emission reductions which result from CCUS technology does China need to be responsible for?". Then, the important influential factors of China's CCUS development are summarized into three aspects (technology maturity, technology sustainability, and external impact factors). Finally, based on these findings, some important comments and suggestions are proposed for the future RD&D of CCUS technology in China.